Pemetaan Risiko Pengembangan Bisnis Dan Strategi Mitigasinya Pada Era Digital: Literature Review - Nadia Dwi Aswita; Emagene Sahasika Azali Sulastiyo; Revalina Nabila Aulia Rahma Putri; Azwa Sahira Nawla; Amanda Syakira Difa Febriani (CV. ITTC INDONESIA, 2026)
The rapid development of digital technology has significantly transformed business activities while simultaneously creating various risks that may affect organizational sustainability. This study aims to map the types of risks encountered in business development and identify mitigation strategies that can be implemented in the digital era. The research employed a literature review method with a qualitative descriptive approach. Relevant literature was collected through Google Scholar and analyzed systematically. The findings reveal that business development risks in the digital era include strategic, operational, financial, reputational, information technology, and data security risks, as well as risks arising from conditions of Volatility, Uncertainty, Complexity, and Ambiguity (VUCA). Furthermore, risk mitigation strategies can be categorized into preventive, reactive, adaptive, and innovative or collaborative approaches. To enhance organizational resilience, the implementation of Enterprise Risk Management (ERM), the utilization of digital technologies, the strengthening of organizational governance, the improvement of risk management literacy, and the development of adaptive capabilities are identified as critical factors. This study concludes that the integration of formal risk management practices with the appropriate use of digital technologies can support business sustainability and strengthen competitiveness in the contemporary digital era.